Integrating technology in literacy instruction : models and frameworks for all learners - Lisenbee, Peggy S.; Pilgrim, Jodi; Vasinda, Sheri (New York : Routledge, 2020)
"This text addresses the changing literacies surrounding students and the need to communicate effectively using technology tools. Technology has the power to transform teaching and learning in classrooms and to promote active learning, interaction, and engagement through different tools and applications. While both technologies and research in literacy are rapidly changing and evolving, this book presents lasting frameworks for teacher candidates to effectively evaluate and implement digital tools to enhance literacy classrooms. Through the lens of Universal Design for Learning (UDL), this text prepares teacher candidates to shape learning environments that support the needs and desires of all literacy learners through the integration of technology and literacy instruction by providing a range of current models and frameworks. This approach supports a comprehensive understanding of the complex multiliteracies landscape. These models address technology integration and demonstrates how pedagogical knowledge, content knowledge, and technological knowledge can be integrated for the benefit of all learners in a range of contexts. Each chapter includes prompts for reflection and discussion to encourage readers to reflect on how literacy and technology can enable teachers to become agents of change, and the book also features Appendices with annotated resource lists of technology tools for students' varied literacy needs in our digital age"--
Includes bibliographical references and index.
Keywords: Computers and literacy; Language arts -- Computer-assisted instruction